Da’wah Communication and the Hijrah Youth Movement: Islamic Identity and Social Change in Bandung - Yusuf, Yogi Muhammad (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to examine how da'wah communication plays a role in shaping social change through the lifestyle of